Pelatihan Pengemasan Usaha Wingko Bakar Klojen untuk Meningkatkan Daya Saing Produk UMKM di Kelurahan Klojen Kota Malang - Wahidyanti Rahayu Hastutiningtyas; Karunia Setyowati Suroto; Cahyo Sasmito (Universitas Tribhuwana Tunggadewi Malang, 2025)
Wingko bakar is one of the traditional foods typical of Java that has excellent potential as an MSME product. In Klojen Village, Malang City, several small entrepreneurs produce wingko bakar but face obstacles in product packaging. This research aims to analyse the impact of packaging training on improving the quality and competitiveness of baked wingko products in Klojen Village. The method employed is a qualitative approach, utilizing participatory observation techniques, in-depth interviews, and documentation. The training will be held for 3 days, covering topics such as packaging design, packaging material selection, hygienic packaging techniques, and branding strategies. The research results show that after attending the training, 85% of participants were able to produce more attractive and hygienic packaging, there was an average increase in turnover of 40%, and the baked wingko product received a positive response from consumers. Packaging training has proven effective in improving the competitiveness of wingko bakar products from MSMEs in Klojen Village.ABSTRAKWingko bakar merupakan salah satu makanan tradisional khas Jawa yang memiliki potensi besar sebagai produk UMKM. Di Kelurahan Klojen, Kota Malang, terdapat beberapa pengusaha kecil yang memproduksi wingko bakar namun mengalami kendala dalam hal pengemasan produk. Penelitian ini bertujuan untuk menganalisis dampak pelatihan pengemasan terhadap peningkatan kualitas dan daya saing produk wingko bakar di Kelurahan Klojen. Metode yang digunakan adalah pendekatan kualitatif dengan teknik observasi partisipatif, wawancara mendalam, dan dokumentasi. Pelatihan dilaksanakan selama 3 hari dengan materi meliputi desain kemasan, pemilihan bahan kemasan, teknik pengemasan higienis, dan strategi branding. Hasil penelitian menunjukkan bahwa setelah mengikuti pelatihan, 85% peserta mampu memproduksi kemasan yang lebih menarik dan higienis, terjadi peningkatan omzet rata-rata sebesar 40%, dan produk wingko bakar mendapat respon positif dari konsumen. Pelatihan pengemasan terbukti efektif dalam meningkatkan daya saing produk UMKM wingko bakar di Kelurahan Klojen.